Colonization During Colonialism: Developing a Framework to Assess the Rapid Ecological Transformation of Mauritius’s Pristine Ecosystem - Seetah, Krish; Manfio, Stefania; Balbo, Andrea; Farr, R. Helen; Florens, F. B. Vincent (Frontiers in Ecology and Evolution, 2022)
The colonization of Mauritius exemplifies the role played by humans in altering the ecosystems of remote oceanic islands. This paper focuses on how we study those islands first colonized under the global mantle of colonialism. Here we aim to provide a theoretical framework for historical ecological investigations to disentangle the processes, impacts, and outcomes of colonization during colonialism, considering local, regional, and global drivers. The paper provides a review of existing literature, outlines a proposed research program encompassing paleoecology, palaeoclimatology, archaeology, and history, and offers details of potential research sites. We present ‘historical ecology’ as a framework to aid future work, and argue that a refined understanding of the impact of human colonization can help create a nuanced chronology of environmental degradation that typifies Mauritius. Such detailed assessment is necessary to inform contemporary ecological conservation efforts. Finally, we argue that narratives of changing ecosystems and practice can help construct ‘usable pasts’, often missing from historical records, for the multicultural populace of the island.